CD8+ T Cell-Mediated Immunity during Trypanosoma cruzi Infection: A Path for Vaccine Development?. (1st July 2014) - dos Santos Virgilio, Fernando; Pontes, Camila; Dominguez, Mariana Ribeiro; Ersching, Jonatan; Rodrigues, Mauricio Martins; Vasconcelos, José Ronnie
Abstract : MHC-restricted CD 8 + T cells are important during infection with the intracellular protozoan parasite Trypanosoma cruzi, the causative agent of Chagas disease. Experimental studies performed in the past 25 years have elucidated a number of features related to the immune response mediated by these T cells, which are important for establishing the parasite/host equilibrium leading to chronic infection. CD 8 + T cells are specific for highly immunodominant antigens expressed by members of the trans -sialidase family. After infection, their activation is delayed, and the cells display a high proliferative activity associated with high apoptotic rates. Although they participate in parasite control and elimination, they are unable to clear the infection due to their low fitness, allowing the parasite to establish the chronic phase when these cells then play an active role in the induction of heart immunopathology. Vaccination with a number of subunit recombinant vaccines aimed at eliciting specific CD 8 + T cells can reverse this path, thereby generating a productive immune response that will lead to the control of infection, reduction of symptoms, and reduction of disease transmission. Due to these attributes, activation of CD 8 + T lymphocytes may constitute a path for the development of a veterinarian or human vaccine.